Effectiveness of various botanical traps against apple snail, Pomacea maculata (Gastropoda: Ampullariidae) in a rice field - R. B., Syamsul; Muhamad Awang, Rita; Gilal, Arfan Ahmed; Gnanasegaram, Manjeri (Universiti Putra Malaysia Press, 2016)
The adverse effects of molluscicides applied for the control of the invasive apple snails, Pomacea spp., have led to the search for eco-based cultural, mechanical and biological control techniques. Therefore, a field study on the relative effectiveness of locally available and cost effective plant-based traps against Pomacea spp. was conducted. Results showed jackfruit skin (9.03 ± 0.60/m2 and 6.03 ± 0.60/m2) and damaged pomelo (9.00 ± 0.61/m2 and 5.78 ± 0.74/m2) were relatively more effective than tapioca leaves, water spinach leaves and old newspaper. Snails also displayed preference for fresh materials as compared to rotten materials. Thus, incorporating these findings in rice fields during early susceptible growth will ease the collection and destruction of snails.